Long-term simulations of thermal and hydraulic characteristics in a mountain massif: The Mont Blanc case study, French and Italian Alps - Marechal, Jean-Christophe; Perrochet, Pierre; Tacher, Laurent (My University, 1999)
The use of hydrothermal simulation models to improve the prediction of water inflows in underground works during drilling is tested in the Mont Blanc tunnel, French and Italian Alps. The negative thermal anomaly that was observed during the drilling of this tunnel in 1960 is reproduced by long-term, transient hydrothermal simulations. Sensitivity analysis shows the great inertia of thermal phenomena at the massif scale. At the time of tunnel drilling, the massif had not reached thermal equilibrium. Therefore, a set of simulation scenarios, beginning at the end of the last glacial period, was designed to explain the anomaly encountered in the tunnel in 1960. The continuous cooling of alpine massifs due to infiltration of waters from the surface has occurred for 12,000 years and is expected to continue for about 100,000 years. Comparisons of water-discharge rates simulated in the tunnel with those observed indicate that this hydrothermal method is a useful tool for predicting water inflows in underground works.
Keywords: crystalline rocks; numerical modeling; France; Italy; thermal conditions; ROCK TEMPERATURES; ALPINE